Individuality, Stability, and Variability of the Plaque Microbiome - Utter, Daniel R.; Mark Welch, Jessica L.; Borisy, Gary G. (Frontiers in Microbiology, 2016)
Dental plaque is a bacterial biofilm composed of a characteristic set of organisms. Relatively little information from cultivation-independent, high-throughput analyses has been published on the temporal dynamics of the dental plaque microbiome. We used Minimum Entropy Decomposition, an information theory-based approach similar to oligotyping that provides single-nucleotide resolution, to analyze a previously published time series data set and investigate the dynamics of the plaque microbiome at various analytic and taxonomic levels. At both the genus and 97% Operational Taxonomic Unit (OTU) levels of resolution, the range of variation within each individual overlapped that of other individuals in the dataset. When analyzed at the oligotype level, however, the overlap largely disappeared, showing that single-nucleotide resolution enables differentiation of individuals from one another without ambiguity. The overwhelming majority of the plaque community in all samples was made up of bacteria from a moderate number of plaque-typical genera, indicating that the overall community framework is shared among individuals. Each of these genera fluctuated in abundance around a stable mean that varied between individuals, with some genera having higher inter-individual variability than others. Thus, at the genus level, differences between individuals lay not in the identity of the major genera but in consistently differing proportions of these genera from mouth to mouth. However, at the oligotype level, we detected oligotype “fingerprints,” a highly individual-specific set of persistently abundant oligotypes fluctuating around a stable mean over time. For example, within the genus Corynebacterium, more than a dozen oligotypes were detectable in each individual, of which a different subset reached high abundance in any given person. This pattern suggests that each mouth contains a subtly different community of organisms. We also compared the Chinese plaque community characterized here to previously characterized Western plaque communities as represented by analyses of data emerging from the Human Microbiome Project, and found no major differences between Chinese and Western supragingival plaque. In conclusion, we found the plaque microbiome to be highly individualized at the oligotype level and characterized by stability of community membership, with variability in the relative abundance of community members between individuals and over time.